Substrate Activity Screening with Kinases: Discovery of Small‐Molecule Substrate‐Competitive c‐Src Inhibitors1. Issue 27 (2nd May 2014) - Breen, Meghan E.; Steffey, Michael E.; Lachacz, Eric J.; Kwarcinski, Frank E.; Fox, Christel C.; Soellner, Matthew B.
Abstract Substrate‐competitive kinase inhibitors represent a promising class of kinase inhibitors, however, there is no methodology to selectively identify this type of inhibitor. Substrate activity screening was applied to tyrosine kinases. By using this methodology, the first small‐molecule substrates for any protein kinase were discovered, as well as the first substrate‐competitive inhibitors of c‐Src with activity in both biochemical and cellular assays. Characterization of the lead inhibitor demonstrates that substrate‐competitive kinase inhibitors possess unique properties, including cellular efficacy that matches biochemical potency and synergy with ATP‐competitive inhibitors.